Turkish Adaptation of the Nursing Students’ Fear Toward Artificial Intelligence Scale: A Study of Validity and Reliability - Şengül Korkmaz Binay; Papatya Karakurt (Journal of Nursing Measurement, 2026)
Background and Purpose: Most nursing students report having limited knowledge about artificial intelligence, which may lead to anxiety and fear regarding its use in clinical practice. This study aimed to examine the validity and reliability of the Turkish adaptation of the Nursing Students’ Fear Toward Artificial Intelligence Scale. Methods: The sample consisted of 402 nursing students enrolled in a faculty of health sciences in the Eastern Anatolia Region between May and July 2025. Linguistic equivalence was established using the translation–back-translation method. Data were analyzed using parametric ( t test) and nonparametric tests (Mann–Whitney U, Kruskal–Wallis, and Spearman correlation) based on distribution characteristics. Validity and reliability were assessed using the Davis technique, coefficient alpha, standardized root-mean-square residual fit indices, and item–total correlation analyses. Results: The content validity index of the Turkish version of the scale was .84. The Kaiser–Meyer–Olkin value was .91, and Bartlett’s test was statistically significant (χ² = 2271.78, p < .001), indicating suitability for factor analysis. The analysis revealed a single-factor structure explaining 57.2% of the total variance. The overall coefficient alpha was .91, with item–total correlations ranging from .57 to .76. Test–retest analysis demonstrated a strong positive correlation between measurements ( r = .78, p < .001). Conclusion: These findings indicate that the Turkish version of the Nursing Students’ Fear Toward Artificial Intelligence Scale is a valid and reliable instrument for assessing nursing students’ fear of artificial intelligence.